Web-based internet searches for digital health products in the United Kingdom before and during the COVID-19 pandemic: a time-series analysis using app libraries from the Organisation for the Review of Care and Health Applications (ORCHA) - Simon Leigh; Tim Andrews; Rob Daly; Sebastian Stevens; Luka Lapajne; Charlotte Clayton; Liz Ashall-Payne (BMJ Open, 2021)
Objectives To explore if consumer interest in digital health products (DHPs), changed following the COVID-19 pandemic and the lockdown measures that ensued.Design Retrospective time-series analysis of web-based internet searches for DHPs in the UK, split over two periods, pre-COVID-19 lockdown (January 2019–23 March 2020) and post-COVID-19 lockdown (24 March 2020–31 December 2020).Setting The UK.Participants Members of the UK general population using health-app libraries provided by the Organisation for the Review of Care and Health Applications.Primary and secondary outcome measures The primary outcome was volume of searches for DHPs. Secondary outcomes considered search volumes for 25 different therapeutic areas. Outcomes were assessed for significance using a two-stage Poisson test.Results There were 126 640 searches for DHPs over the study period. Searches for DHPs increased by 343% from 2446 per month prior to COVID-19 lockdown measures being introduced to 8996 per month in the period following the first COVID-19 lockdown in the UK. In total, 23/25 (92%) of condition areas experienced a significant increase in searches for DHPs, with the greatest increases occurring in the first 2 months following lockdown. Musculoskeletal conditions (2,036%), allergy (1,253%) and healthy living DHPs (1,051%) experienced the greatest increases in searches compared with pre-lockdown. Increased search volumes for DHPs were sustained in the 9 months following the introduction of lockdown measures, with 21/25 (84%) of condition areas experiencing monthly search volumes at least 50% greater than pre-lockdown levels.Conclusions The COVID-19 pandemic has profoundly disrupted the routine delivery of healthcare, making face-to-face interaction difficult, and contributing to unmet clinical needs. This study has demonstrated significant increases in internet searches for DHPs by members of the UK population since COVID-19, signifying an increased interest in this potential therapeutic medium. Future research should clarify whether this increased interest has resulted in increased acceptance and utilisation of these technologies also.